Dexrazoxane provided moderate protection in a catecholamine model of severe cardiotoxicity - Zatloukalová, Libuše; Filipský, Tomáš; Mladěnka, Přemysl; Semecký, Vladimír; Macáková, Kateřina; Holečková, Magdalena; Vávrová, Jaroslava; Palicka, Vladimir; Hrdina, Radomír (Canadian journal of physiology and pharmacology, 2012)
Positive effects of dexrazoxane (DEX) in anthracycline cardiotoxicity have been mostly assumed to be associated with its iron-chelating properties. However, this explanation has been recently questioned. Iron plays also an important role in the catecholamine cardiotoxicity. Hence in this study, the influence of DEX on a catecholamine model of acute myocardial infarction (100 mg/kg of isoprenaline by subcutaneous injection) was assessed: (i) the effects of an intravenous dose of 20.4 mg/kg were analyzed after 24 h, (ii) the effects were monitored continuously during the first two hours after drug(s) administration to examine the mechanism(s) of cardioprotection. Additional in vitro experiments on iron chelation/reduction and influence on the Fenton chemistry were performed both with isoprenaline/DEX separately and in their combination. DEX partly decreased the mortality, reduced myocardial calcium overload, histological impairment, and peripheral haemodynamic disturbances 24 h after isoprenaline administration. Continuous 2 h experiments showed that DEX did not influence isoprenaline induced atrioventricular blocks and had little effect on the measured haemodynamic parameters. Its protective effects are probably mediated by inhibition of late myocardial impairment and ventricular fibrillation likely due to inhibition of myocardial calcium overload. Complementary in vitro experiments suggested that iron chelation properties of DEX apparently did not play the major role.
Keywords: modely nemocí na zvířatech; Isoproterenol; Calcium; Male; Rats, Wistar; vápník; železo; Myocardium; Iron Chelating Agents; chelátory železa; mužské pohlaví; potkani Wistar; infarkt myokardu; Hemodynamics; krysa rodu Rattus; Cardiotonic Agents; Animals; Iron; zvířata; Myocardial Infarction; Rats; Disease Models, Animal; kardiotonika; isoprenalin; razoxan; hemodynamika; myokard; Razoxane